Perbaikan Balok Beton Bertulang dengan Metode Jacketing dengan Bahan Ferosemen Akibat Beban Siklik pada Beban Ultimit - Bagus Soebandono , Andreas Triwiyono, Muslikh (Universitas Muhammadiyah Yogyakarta, 2011)
A large number of buildings construction was made of reinforced concrete structure, composed of concrete and steel. The reinforced concrete structure elements could experience damage due to earthquake, from light to heavy failure, such as heavy bending-shear crack near the beam column joint. It is necessary, therefore, to repair the structure adopted good method and workability. The specimens were part of exterior beam-column joint model. Cyclic lateral load was applied to simulate earthquake load. This research used 3 specimens: US-1, the shear damage specimen as the result of first-step loaded test, then are repaired by using 1 layer rectangular galvanized welded wire mesh became R-US.1. US-2, the shear damage specimen as the result of first-step loaded test, then are repaired by using 2 layers rectangular galvanized welded wire mesh became R-US.2. UBB, the bending damage specimen as the result of first-step loaded test, then are repaired by using 2 layers rectangular galvanized welded wire mesh became R-UBB. The result showed that the retrofitted on ultimate load by using jacketing ferrocement increased the ultimate strength capacity of 91,667%(US-1 to R-US.1), 81,818%(US-2 to R.US.2) and 28,571%(UBB to R-UBB) respectively. Increasing the hysteretic energy were 215, 66%(US-1 to R-US.1), 273,11%(US-2 to R.US-2) and 389, 84%(UBB to R-UBB). The ductility of retrofitted specimen 6,64(R-US.1) and 12,72(R-US.2). The initial stiffness of retrofitted specimens decreased 60%(US-1 to R-US.1), 40%(US-2 to R-US.2) and 18%(UBB to R-UBB).